RESEARCH IN THE FIELD OF SMALL CONSTRUCTION OF DAMS AND PROSPECTS FOR THE USE OF DRAIN OF SMALL MOUNTAIN RIVERS OF DAGESTAN - A. S. Ragimova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
This article contains a scientific analysis of the relevance in the field of small construction of dams and prospects for the use of drain of small mountain rivers of Dagestan.